Practice, attitudes and views of right to access of sexual and reproductive health services by LGBTQI among primary health care nurses in Tshwane - Raikane J. Seretlo; Mathildah M. Mokgatle (AOSIS, 2023)
Background: Sexual and reproductive healthcare services (SRHS) are crucial investments for improving individual well-being and granting an opportunity to exercise sexual and reproductive rights. Primary health care (PHC) nurses are described as gatekeepers, preventing many individuals, including the members of the lesbian, gay, bisexual, transgender, queer and intersex (LGBTQI) community, from accessing much-needed healthcare services. Aim: The study aimed at exploring the experiences and perceptions of PHC nurses during the provision of SRHS for members of the LGBTQI community. Setting: The study was conducted among eight clinics around Tshwane in South Africa. Methods: Twenty-seven professional nurses were selected purposively, using an exploratory design approach. A semistructured interview guide and in-depth face-to-face interviews were used to gather data. Data were analysed using thematic content analysis (TCA). Results: Four themes emerged: understanding of SRHS, attitudes of PHC nurses, frequency of rendering services based on utilisation of SHR and views of nurses on the right to access SRHS. Conclusion: A heteronormative approach was mostly indicated when rendering SHRS to the members of the LGBTQI community. Members of the LGBTQI community do not use the SRHS as often as heterosexual patients; lack of training, skills and knowledge were identified as barriers to rendering much-needed SRHS for members of the LGBTQI community. Contribution: The findings of this study assisted in demonstrating the PHC nurses' perceptions, experiences, skills and knowledge of LGBTQI SRHS, thus improving the members of the LGBTQI community's accessibility and utilisation of SRHS.